The sense of safety theoretical framework: a trauma-informed and healing-oriented approach for whole person care - Lynch, Johanna M.; Stange, Kurt C.; Dowrick, Christopher; Getz, Linn; Meredith, Pamela J.; Van Driel, Mieke L.; Harris, Meredith G.; Tillack, Kate; Tapp, Caley (Frontiers in Psychology, 2025)
ObjectivesThis research describes four aspects of the development of the Sense of Safety Theoretical Framework for whole person care: exploring the meaning of the phrase “sense of safety”—the whole person language; the range of human experience that impacts sense of safety—whole person scope; the dynamics that build sense of safety—the healing goals; and the personal and cross-disciplinary trauma-informed practitioner skills and attitudes that facilitate sense of safety.MethodsThis qualitative participatory study was conducted in two phases. Researchers iteratively explored the concept of sense of safety using focus groups and semi-structured interviews. Overarching research questions were: “Does the transdisciplinary concept of Sense of Safety make sense as an approach to the whole person in distress?”; “How do participants describe the meaning of the phrase “sense of safety”?”; “What does a person experience when they feel safe?” and “What can practitioners do to facilitate a sense of safety?” Phase One involved rural and urban family doctors, mental health clinicians across multiple disciplines, people with lived experience of mental distress, and Indigenous Australian academics. Phase Two widened the scope of disciplines involved to iteratively reflect on their clinical and personal experience with “sense of safety” and included international family doctors, physiotherapists, occupational therapists, social workers, teachers, multidisciplinary rural clinicians and multidisciplinary clinicians with a lived experience of physical trauma, grief, and severe mental illness.ResultsThe everyday language “sense of safety” was found to describe a whole person experience that integrates awareness of self, others, and context. The scope of human experience that impacts sensed safety was found to include seven domains: Environment, Social Climate, Relationships, Body, Inner Experience, Sense of Self and Spirit/Meaning (Whole Person Domains). Five dynamic healing goals were identified that build sense of safety: Broad Awareness; Calm Sense-Making; Respectful Connection; Capable Engagement; and Owning Yourself (Sense of Safety Dynamics). Five practitioner skills and attitudes that facilitate sense of safety were named: Valuing the Whole Picture; Holding Story Safely; Being with You; Learning Together; and Validating Dignity (Sense of Safety Practitioner Skills).ConclusionThe Sense of Safety Theoretical Framework developed in this study focusses on an experience that is a fundamental prerequisite of health. Sense of safety is affected by, and influences, life story, relationships, meaning, sense of self, and – physical health: the whole person. The language “sense of safety” communicates an integrative experience that can help clinicians to see the whole person and describe a cross-disciplinary goal of care. The Whole Person Domains clarify the scope of care required, while the Sense of Safety Dynamics offer practical processes of care. The Sense of Safety Practitioner Skills describe trauma-informed skills and attitudes that facilitate a sense of safety. Each of these parts of the Sense of Safety Theoretical Framework translate practitioner, lived experience, and First Nations wisdom and a wide existing transdisciplinary literature into a framework and language ready for practice. Assessing and building sense of safety prioritizes a healing-oriented and trauma-informed approach. The Sense of Safety Theoretical Framework facilitates a paradigm shift that towards integrating sensation, subjective experience, physiology, and social determinants into everyday quality care in health, education and public policy.